The Impact of a Diabetes Self-Management Education Program Provided through a Telemedicine Link to Rural California Health Care Clinics - Jim Nuovo (SAGE Publishing, 2013)
Background This project investigated the impact of a DM self-management education program provided through a telemedicine link at nine rural health clinics in Northern California. Methods Two hundred thirty nine patients were provided with a single 2-hour class on DM delivered through a live televideo connection. Patients provided pre-intervention information on: demographics and overall health, self-care behaviors, and knowledge about DM. All participants completed a post-education survey on knowledge and self-care behaviors. Results There was a significant decrease in the number of patients who felt overwhelmed with their DM; pre-intervention 18.8%; post-intervention 5.4% ( P < 0.0001). Patients increased the number of days they exercised; pre-intervention 3.4 days; post-intervention 3.9 days ( P = 0.02). Patients increased the number of days they checked their feet; pre-intervention 4.2 days; post-intervention 5.6 days ( P < 0.01). Knowledge about DM improved over the study period ( P < 0.01). Conclusions A single 2-hour class on DM administered through a telemedicine link to patients in rural health clinics resulted in feeling less overwhelmed, more knowledgeable about DM, and demonstrated an increase in self-care behavior; ie, exercise and foot care.